Effectiveness of Palm Sap (Borassus flabellifer L.) Concentrations on the Growth of Dendrobium welirang Orchids - Satriani, Slamet; Mulyaningrum, Eko Retno; Nurwahyunani, Atip (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to evaluate the effectiveness of palm sap (Borassus flabellifer L.) as an organic plant growth regulator on the vegetative growth of Dendrobium welirang orchids. Palm sap contains natural sugars, minerals, and biologically active components that may serve as an organic plant growth regulator. The research was conducted at the Candi Orchid Greenhouse in Semarang from July to October 2024 using a Completely Randomized Design with four palm sap concentrations, namely 0, 100, 150, and 200 ml/l, each applied in five replications. Observed parameters included plant height and root length. Data were analyzed using One Way ANOVA at a 5% significance level, followed by the Duncan Multiple Range Test. The results showed that palm sap concentration significantly affected plant height with the growth o1bserved in treatment P3 showing an average result of 12.01 cm. In contrast, root length was not significantly affected. These findings indicate that palm sap has potential as an environmentally friendly organic plant growth regulator to support vegetative growth of Dendrobium welirang orchids.